2013
DOI: 10.1186/1471-2458-13-820
|View full text |Cite
|
Sign up to set email alerts
|

Parental food-related behaviors and family meal frequencies: associations in Norwegian dyads of parents and preadolescent children

Abstract: BackgroundFrequent family meals are associated with healthy dietary behaviors and other desirable outcomes in children and adolescents. Therefore, increased knowledge about factors that may increase the occurrence of family meals is warranted. The present study has its focus on the home food environment, and aims to explore potential associations between parent-reported feeding behaviors and child-reported family meal frequencies.MethodsCross-sectional surveys were performed among 10-12-year-olds and their par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 55 publications
4
16
0
Order By: Relevance
“…In particular, the feeding variable healthy home food environment seems to be essential. The importance of a healthy home food environment is also discussed by Melbye et al [ 32 ] who found a positive association between this variable and the frequency of shared family meals (which is positively associated with child healthy eating) and who suggested that parents providing a healthy home food environment will perhaps be more inclined to see the importance of sharing meals with their children. Correspondingly, we suggest that parents providing a healthy home food environment may be more liable to see the importance of encouraging their children to have a balanced and varied diet and to teach them about nutrition.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, the feeding variable healthy home food environment seems to be essential. The importance of a healthy home food environment is also discussed by Melbye et al [ 32 ] who found a positive association between this variable and the frequency of shared family meals (which is positively associated with child healthy eating) and who suggested that parents providing a healthy home food environment will perhaps be more inclined to see the importance of sharing meals with their children. Correspondingly, we suggest that parents providing a healthy home food environment may be more liable to see the importance of encouraging their children to have a balanced and varied diet and to teach them about nutrition.…”
Section: Discussionmentioning
confidence: 97%
“…Rather, it suggests that hunger is a more ubiquitous problem, and while concentrated within impoverished families and a spectrum of schools who serve socio-economically disadvantaged populations, it is not unique to them. Hunger crosses cultures and populations, and feeding the hungry in all parts of society should always remain a priority (US Department of Agriculture 2013 ; Melbye et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in adolescence predisposes a young person to heart disease, type 2 diabetes, stroke, several types of cancer and osteoarthritis (2, [12][13][14][15][16]. It has also been suggested that obesity in adolescence may adversely affect academic performance (12)(13)(14)(16)(17)(18)(19)(20)(21). It is important to remember that obesity and nutritional deficiencies are not mutually exclusive, there may be a double burden for many of both obesity and nutrient deficiencies (such as iron deficiency and zinc deficiency) (11,22).…”
Section: Introductionmentioning
confidence: 99%